Analysis of the prospects of new therapeutic agents for the treatment of rheumatoid arthritis: New therapeutic agents for rheumatoid arthritis - Blagov, Alexander V.; Orekhov, Nikolay A.; Beloyartsev, Dmitry F.; Churov, Alexey V.; Kovyanova, Tatiana I.; Starodubtseva, Irina A.; Sukhorukov, Vasily N.; Orekhov, Alexander N. (Cellular and Molecular Biology, 2025)
Rheumatoid arthritis (RA), a chronic autoimmune disease, is one of the major research themes in medicine. The current therapies have their limitations and cannot completely cure RA, but new therapeutic strategies are being proposed to reduce the shortcomings of approved drugs. This review will consider new potential treatment strategies for RA, including T-cell therapy, genetic editing and epigenetic regulation, what advantages and disadvantages they have and to what pathological target in RA they are directed.